Graft dysfunction is associated with late CMV infection after kidney transplantation - Zeng, Angela; Barraclough, Katherine; Lian, Michael; Masterson, Rosemary; Hughes, Peter; Chow, Kevin V. (Frontiers in Transplantation, 2025)
BackgroundCytomegalovirus (CMV) causes significant morbidity and mortality following kidney transplantation. Late CMV infection (≥2 years post-transplant) is uncommon, and its risk factors and outcomes may differ from earlier infection.MethodsWe conducted a single-centre retrospective study of kidney transplant recipients between 2009 and 2019. Patients were grouped by CMV status: no infection, early infection (<2 years post-transplant), and late infection (≥2 years post-transplant). Clinical characteristics and outcomes were compared.ResultsDonor-positive/recipient-negative (D+/R−) serostatus was observed in 105/710 (14.8%) patients without CMV, 28/42 (66.7%) with early CMV, and 2/28 (7.1%) with late CMV (p < 0.001). Prior rejection occurred in 5.9%, 16.7%, and 10.7% respectively (p = 0.017). Median serum creatinine was 113.0, 127.5, and 219.5 µmol/L respectively (p < 0.001). CMV serostatus was significantly associated with early infection (p < 0.001), while only serum creatinine was associated with late infection (p = 0.003). Trends were seen toward better one-year patient survival (97.6% vs. 85.7%, p = 0.051) and graft survival (88.1% vs. 71.4%, p = 0.073) after early vs. late infection.ConclusionsRisk factors for CMV infection differ by timing post-transplant. Renal dysfunction may be a key predictor of late infection. identifying at-risk patients may support targeted surveillance and improve long-term outcomes.